A Comparison of Cognitive Emotion Regulation in Children with and without ADHD - Ahmadi, Saba; nouri, elham; moradian tizabi, maryan (Iranian Journal of Neurodevelopmental Disorders, 2023)
Background and Purpose: One of the areas in which children with ADHD are challenged is cognitive emotion regulation. The current study defines as its purpose the comparison of Cognitive Emotion Regulation in Children with and without ADHD. Method: This study is a survey conducted through the descriptive research methodology. The statistical population includes all children with and without ADHD currently (2021-2022) studying in the city of Tehran. Of these children, 100 have been selected through purposive sampling (50 regular children and 50 children with ADHD) ranging from 14-18 years old. To collect the study’s data, the shortened version of Garnefski et al.’s Cognitive Emotion Regulation Questionnaire (2006) has been employed. The data has been analyzed through SPSS V.26 and independent t-test. Results: The results of the independent t-test shows that the difference between cognitive emotion regulation of children with and without ADHD is statistically significant (P